ANALISIS KEPUASAN PERSPEKTIF KUALIAS PELAYANAN - Mr Warsono (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The main business of a bank is trust. Therefore, all efforts are made to serve, and satisfy customers, one of which presents quality service. This study aims to analyze the effect of service quality on customer satisfaction. To prove this research, the quantitative, descriptive, and linear regression analysis methods are used. The object of research is Eximbank, sampling technique using accidental sampling, the number of respondents 109, and data collection techniques using questionnaire. The results showed that service quality affected satisfaction. That is, customer loyalty depends on what consumers feel, and quality service is the best way to approach